Study of Disinfectant Resistance Genes in Ocular Isolates of Pseudomonas aeruginosa - Dinesh Subedi; Ajay Kumar Vijay; Mark Willcox (MDPI AG, 2018)
Background: The prevalence of disinfectant resistance in Pseudomonas aeruginosa is on the rise. P. aeruginosa is the most common bacteria isolated from cases of microbial keratitis. Many multi-purpose contact lens disinfectant solutions are available to decontaminate contact lenses before use and to help reduce the incidence of infections. However, with increasing disinfectant resistance, the effect of multi-purpose disinfectant solutions may diminish. The goal of this study was to examine genes associated with disinfectant resistance in ocular isolates of P. aeruginosa and understand the strain’s susceptibility to different multipurpose disinfectant solutions. Methods: Seven potential disinfectant resistance genes were used in BLASTn searches against the whole genomes of 13 eye isolates of P. aeruginosa. A microdilution broth method was used to examine susceptibility to four different multipurpose disinfectant solutions. Results: All strains possessed the sugE2, sugE3 and emrE (qacE) genes. The sugE1 and qacEdelta1 genes were present in 6/13 isolates. No strains contained the qacF or qacG genes. All tested disinfectant solutions had the ability to kill all test strains at 100% concentration, with some strains being susceptible at 1:8 dilutions of the disinfecting solutions. However, the presence of disinfectant resistance genes was not associated with susceptibility to multi-purpose disinfectants. Conclusion: All four tested contact lens disinfectant preparations are effective against P. aeruginosa isolates regardless of the presence of disinfectant resistance genes.